2019
DOI: 10.3168/jds.2018-15212
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Proinflammatory gene expression relative to the collection technique of endometrial samples from cows with and without subclinical endometritis

Abstract: Uterine inflammation negatively affects reproductive performance and is an important cause of infertility and subfertility in dairy cows. Several studies have investigated the use of gene expression in endometrial samples collected by biopsy or cytology to evaluate the inflammatory response of the cow uterus. This study aimed to compare the expression of the CCL5, CXCL8, IL6, and IL1B genes in the bovine endometrium according to the site of sample collection [caruncular (C) or intercaruncular (IC)], the collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In contrast,Shaheen et al (2020) observed an increase in the levels of cytokines as IL-2 and IL-6 in lactating crossbreed cows diagnosed with CM. Interestingly, no difference in the expression of chemokine CCL5 was observed between healthy, RP and CM groups Fagundes et al (2019). found no differences in the expressions of CCL5 in cows when caruncular and intercaruncular regions of the endometrial epithelium were compared in cases of absent or mild in ammation; however, the expression was higher in endometrium with severe in ammation when compared to groups with mild in ammation or none.In this study, we aimed to nd a relationship between the expression of steroidogenic genes andpostpartum immune function.…”
mentioning
confidence: 76%
“…In contrast,Shaheen et al (2020) observed an increase in the levels of cytokines as IL-2 and IL-6 in lactating crossbreed cows diagnosed with CM. Interestingly, no difference in the expression of chemokine CCL5 was observed between healthy, RP and CM groups Fagundes et al (2019). found no differences in the expressions of CCL5 in cows when caruncular and intercaruncular regions of the endometrial epithelium were compared in cases of absent or mild in ammation; however, the expression was higher in endometrium with severe in ammation when compared to groups with mild in ammation or none.In this study, we aimed to nd a relationship between the expression of steroidogenic genes andpostpartum immune function.…”
mentioning
confidence: 76%
“…When using the same in vitro model as Guo et al (2019), changes in proteins related to the above pathways were also observed (Piras et al, 2017). In vivo, cows with SCE present increased local gene expression of proinflammatory cytokines characteristic of acute inflammatory processes (Kasimanickam et al, 2014;Fagundes et al, 2019;Pereira et al, 2020). In addition, cows affected by endometritis exhibit a large number of genes involved in immune response, cell adhesion, chemotaxis, apoptosis, and G-protein coupled receptor signaling pathways differentially expressed compared with healthy cows (Salilew-Wondim et al, 2016).…”
Section: Introductionmentioning
confidence: 83%
“…However, to date, gene expression studies aiming to analyze the effects of SCE from in vivo material were either based on biopsy-derived whole-endometrium tissue (Salilew-Wondim et al, 2016;Raliou et al, 2019) or endometrial swab or cytobrush samples (Kasimanickam et al, 2014;Fagundes et al, 2019), without discriminating between endometrial cell types. The bovine endometrium is a complex and heterogeneous tissue, and quantification of gene transcription from the whole endometrium may not reflect cell-specific transcription.…”
Section: Introductionmentioning
confidence: 99%
“…It is likely, therefore, that CNP either affects the differentiation of Three of the molecules tested in the current study may participate in modification of embryonic development caused by specific inflammatory events in the endometrium. Both IL6 and IL8 are among the genes whose expression is increased in bovine endometrium associated with subclinical endometritis (Fagundes et al, 2019) and CNP is a constituent of bull seminal plasma (Chrisman et al, 1993). More research is required but evidence from this and other experiments would indicate that CNP and IL-6 would be facilitatory to embryo survival given the effects of CNP (this study) and IL-6 to increase ICM cell number and of IL-6 to activate JAK/STAT signaling in ICM this study).…”
Section: Discussionmentioning
confidence: 99%
“…C-Natriuretic peptide is also present in bull seminal plasma (Chrisman et al, 1993) and could conceivably be one of the mediators of seminal plasma effects on the endometrium or embryo (Bromfield, 2018). Interleukin-8 is one of the cytokines whose expression can be upregulated in females experiencing uterine inflammation or infectious disease (Fagundes et al, 2019;Helfrich et al, 2020) as well as exposure to sperm (Akthar et al, 2020). The primary objective of the current experiments was to evaluate actions of these molecules to increase the capacity of the bovine embryo to develop to the blastocyst stage.…”
Section: Introductionmentioning
confidence: 99%